Biomimetic polymer-based Ag nanocomposites as a antimicrobial platform. (September 2016) - Kung, Mei-Lang; Lin, Pei-Ying; Peng, Shi-Wei; Wu, Deng-Chyang; Wu, Wen-Jeng; Yeh, Bi-Wen; Tai, Ming-Hong; Hung, Huey-Shan; Hsieh, Shuchen
Graphical abstract: The Ag NPs was modified onto the dopamine-deposited substrate (Dopamine/Ag nanocomposite), which shows the excellent toxicity for bacterial cells and selective retains the biocompatible and harmless for endothelial cells. Dopamine/Ag nanocomposite thereby could be a potential substrate for medical devices and/or intra-catheters. Highlights: A simple and green approach to prepare a dopamine-functionalized Ag nanocomposite. Dopamine/Ag nanocomposite owns an excellent antibacterial efficiency. Dopamine/Ag nanocomposite reveals the biocompatible for endothelial cells. The nanocomposite may provide a safety and efficiency strategy for medical devices. Abstract: Dopamine, a component of marine mussel adhesive proteins, plays an important role in various fields such as biosensors, bioelectronics, as well as tissue and pharmaceutical engineering. In this study, we describe a simple approach to prepare a dopamine-functionalized Ag nanocomposite. Using AFM, XPS, and SEM analysis, we demonstrated that dopamine is effectively coated onto a glass substrate and that silver (Ag) nanoparticles are successfully attached and well dispersed on the dopamine-covered glass. Furthermore, absorbance analysis, adhesion assay, and Kirby-Bauer disc diffusion tests are show that the dopamine/Ag nanocomposite exhibits good antibacterial efficiency and inhibits bacterial cell adhesion. The biocompatibility of the nanocomposites towards endothelial cells was also assessed using the MTT assay. The present data show that dopamine/Ag nanocomposites are selective compatible with endothelial cells and toxic for bacterial cells. The findings of the present study can thus support a safe and efficient strategy to develop medical devices and intra-devices or intra-catheters for the prevention of nosocomial and catheter-mediated blood-stream infections and/or endothelial injury complications.